2015
DOI: 10.1016/j.celrep.2015.02.044
|View full text |Cite
|
Sign up to set email alerts
|

Cilia Disassembly with Two Distinct Phases of Regulation

Abstract: Cilia and flagella are dynamic organelles that undergo assembly and disassembly during each cell cycle. They are structurally polarized, and the mechanisms by which these organelles are disassembled are incompletely understood. Here, we show that flagellar resorption occurs in two distinct phases of length-dependent regulation. A CDK-like kinase, encoded by flagellar shortening 1 (FLS1), is required for the normal rate of disassembly of only the distal part of the flagellum. Mechanistically, loss of function o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
60
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 40 publications
(69 citation statements)
references
References 53 publications
7
60
1
Order By: Relevance
“…Previously published protocols were followed [61]. For immunofluorescence, cells were fixedin4% paraformaldehyde, permeabilized with 0.5% NP40, resuspended in MT buffer, and attached to a 10 well slide previously coated with 0.1% polyethyleneimine and extracted with methanol at -20°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…Previously published protocols were followed [61]. For immunofluorescence, cells were fixedin4% paraformaldehyde, permeabilized with 0.5% NP40, resuspended in MT buffer, and attached to a 10 well slide previously coated with 0.1% polyethyleneimine and extracted with methanol at -20°C for 10 min.…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that the length of cilia changes in conditions such as injury [44] or inflammation [45], influences cell cycle time [19, 46] and that shortening of PC induces a phosphorylation signaling cascade [47]. It has been therefore been speculated that the information of axonemal length may be sent into the cytosol and that this signal may be able to regulate the cell cycle re-entry [48], nominating PC as a tumor suppressor that potentially transmits cytostatic signals to the cell [39].…”
Section: Discussionmentioning
confidence: 99%
“…They also suggest that ciliary resorption is a novel checkpoint for G 1 -S transition (Kim and Tsiokas 2011; Sung and Li 2011). In support of this view, several molecules important for ciliary resorption, including Aurora A, HDAC6, centrosomal-P4.1-associated protein (CPAP), and FLS1/CKDL5, have been shown to be vital for cell-cycle progression (Li et al 2011; Hu et al 2015; Gabriel et al 2016). …”
Section: Ciliary Dynamics In Cell-cycle Progressionmentioning
confidence: 95%